STRATEGIES IN TEACHING LITERATURE IN ENGLISH CLASSROOM - Maulizan ZA (Jurnal Visipena, 2014)
This essay discusses about some strategies in teaching literature in English classroom, focusing on teaching poems, prose, and plays. There are some strategies can be applied by the lecturer in teaching literature in English classroom. First of all, the lecturer should prepare the material presented to the students in the class. Secondly, lecturer can set some questions. Thirdly, always ask "why". Fourth, add fuel to the fire. Fifth, add history to the material. Sixth, involve every single student. Seventh, grade the thought, not the content. Eighth, give appropriate homework. Ninth, emphasize references. Tenth, read out the work of other scholars and finally, enjoy the experience. Then some possible way and solution are suggested in teaching literature as the example as follows; first, strategies and procedures in teaching poem entitled “Richard Cory” by Edwin Arlington Robinson , second, strategies and procedures in teaching prose entitled “Sorry, wrong number”, third, strategies and procedures in teaching play entitled “Sense and Sensibility.”